Answer:
a) [tex]H(\frac{1+r}{1-r})[/tex]
b) [tex]t=\sqrt{\frac{2H}{g}\left ( \frac{1+r}{1-r} \right )}[/tex]
c) The ball never gets velocity 0.
Step-by-step explanation:
a)
Assuming the initial height is H meters we have the total distance traveled is
H + distance traveled 1st bounce + distance traveled 2nd bounce+ distance traveled 3rd bounce +...(and so on)
The distances traveled in each bounce are
[tex]\large \left[\begin{array}{ccc}Bounce&distance\; traveled\\1&2rH\\2&2r^2H\\3&2r^3H\\....&....\\n&2r^nH\\...&... \end{array}\right][/tex]
So, the total distance traveled is
[tex]\large H+2rH+2r^2H+2r^3H+...=H(1+2(r+r^2+r^3+...))[/tex]
but
[tex]\large r+r^2+r^3+...=\sum_{k=1}^{\infty}r^k[/tex]
is a convergent geometric series (without the first term=1) which converges to
[tex]\large \frac{1}{1-r}-1[/tex]
and we have that the total distance traveled is
[tex]H(1+2(\frac{1}{1-r}-1))=\boxed{H(\frac{1+r}{1-r})}[/tex]
b)
Since the total time t traveled by the ball is given by the second equation of motion
[tex]\large H(\frac{1+r}{1-r})=\frac{gt^2}{2}[/tex]
we then have
[tex]\large H(\frac{1+r}{1-r})=\frac{gt^2}{2}\rightarrow t^2=\frac{2H}{g}\left ( \frac{1+r}{1-r} \right )[/tex]
and finally
[tex]\large t=\sqrt{\frac{2H}{g}\left ( \frac{1+r}{1-r} \right )}[/tex]
c)
At bounce number n the velocity would be [tex]\large -(k)^nv[/tex] and we know
[tex]\large \lim_{n\to \infty}k^n=0[/tex]
for 0 < k < 1.
So, theoretically speaking, the ball will never have velocity zero, but will become smaller and smaller until it becomes zero in the infinite.